Low attainers in primary mathematics : the whisperers and the maths fairy - Houssart, Jenny (RoutledgeFalmer, 2004)
In this fascinating book, Jenny Houssart draws on close observation with children in lower mathematics sets in primary schools to investigate why some children opt out of mathematics at an early age.